Septicemia: As a result of erroneous parenteral administration of probiotic - R S, AJMAL; BENIWAL, MUKESH KUMAR; SENGAR, G S (Indian Journal of Case Reports, 2022)
Probiotics are formulations of live microbial cells that are administered orally to contribute to intestinal microbial balance. Bacillus clausii is one such aerobic, spore-forming bacterium that is able to survive in the acidic environment of the stomach and is used as a probiotic. In the past few years, probiotic use has increased to a greater extent. However, there is growing global evidence that the use of probiotics in patients with organ failure, the immunocompromised state can cause infections, but it is extremely rare in immunocompetent persons when given through peroral route. However, it can cause severe sepsis in even immunocompetent individuals when given intravenously inadvertently. This case report shows the importance of establishing safety guidelines for probiotic use and particularly for dispensing probiotics in liquid formulations.